Validation of satellite sounder environmental data records: Application to the Cross‐track Infrared Microwave Sounder Suite. Issue 24 (26th December 2013) - Nalli, Nicholas R.; Barnet, Christopher D.; Reale, Anthony; Tobin, David; Gambacorta, Antonia; Maddy, Eric S.; Joseph, Everette; Sun, Bomin; Borg, Lori; Mollner, Andrew K.; Morris, Vernon R.; Liu, Xu; et al.
<x xml:space="preserve">Abstract</x> [1] The Joint Polar Satellite System (JPSS) Cross‐track Infrared Microwave Sounder Suite (CrIMSS) is an advanced operational satellite sounding system concept comprised of the Cross‐track Infrared Sounder and the Advanced Technology Microwave Sounder. These are synergistically designed to retrieve key environmental data records (EDR), namely atmospheric vertical temperature, moisture, and pressure profiles. CrIMSS will serve as the low‐Earth orbit satellite sounding system, starting with the Suomi National Polar‐orbiting Partnership (S‐NPP) satellite and spanning the JPSS‐1 and JPSS‐2 satellites. This paper organizes the general paradigm for validation of atmospheric profile EDR retrieved from satellite nadir sounder systems (e.g., CrIMSS) as a synthesis of complementary methods and statistical assessment metrics. The validation methodology is ordered hierarchically to include global numerical model comparisons, satellite EDR intercomparisons, radiosonde matchup assessments (conventional, dedicated, and reference), and intensive campaign "dissections." We develop and recommend the proper approach for computing profile statistics relative to correlative data derived from high‐resolution in situ data (viz., radiosondes) reduced to forward model layers. The standard statistical metrics used for EDR product assessments on "coarse layers" are defined along with an overview of water vapor weighting schemes and the use of averaging kernels. We then overview the application of the methodology to CrIMSS within the context of the JPSS calibration/validation program, with focus given to summarizing the core data sets to be used for validation of S‐NPP sounder EDR products.